2017
DOI: 10.1111/jsap.12647
|View full text |Cite
|
Sign up to set email alerts
|

Canine pancytopoenia in a Mediterranean region: a retrospective study of 119 cases (2005 to 2013)

Abstract: Infectious diseases appear to be the leading causes of canine pancytopoenia in endemic areas; severe leukopoenia (ehrlichiosis, parvoviral enteritis), thrombocytopoenia (ehrlichiosis) and hypoproteinaemia (parvoviral enteritis), represented potentially useful disease-specific diagnostic determinants. The severity of pancytopoenia significantly affects the clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
6
0
2
Order By: Relevance
“…Preliminary data, published in a proceeding abstract, indicated that approximately 39.2% of dogs diagnosed with leishmaniosis were concurrently exposed to E canis in Greece . The clinical and clinicopathologic manifestations of CME could overlap substantially with those of canine leishmaniosis and other vector‐borne diseases, complicating the diagnosis . In this study, the lack of an association between E canis seropositivity and L infantum infection in sick dogs, minimizes the possibility of a confounding effect of the latter between E canis seropositivity and the evaluated clinicopathologic abnormalities.…”
Section: The Associations Between the Presence Of Anti‐ehrlichia Canimentioning
confidence: 91%
See 1 more Smart Citation
“…Preliminary data, published in a proceeding abstract, indicated that approximately 39.2% of dogs diagnosed with leishmaniosis were concurrently exposed to E canis in Greece . The clinical and clinicopathologic manifestations of CME could overlap substantially with those of canine leishmaniosis and other vector‐borne diseases, complicating the diagnosis . In this study, the lack of an association between E canis seropositivity and L infantum infection in sick dogs, minimizes the possibility of a confounding effect of the latter between E canis seropositivity and the evaluated clinicopathologic abnormalities.…”
Section: The Associations Between the Presence Of Anti‐ehrlichia Canimentioning
confidence: 91%
“…Numerous clinicopathologic abnormalities including anemia, thrombocytopenia, leukopenia, pancytopenia, and hyperproteinemia were associated with E canis seropositivity in this study, and seropositive dogs had lower HCTs, and WBC and platelet counts compared with the seronegative dogs. All of those changes have been consistently described in CME, and they could represent clinically relevant indicators of exposure to or active infection by E canis . In contrast, Costa et al (2007) found no association between HCTs and E canis seropositivity …”
Section: The Associations Between the Presence Of Anti‐ehrlichia Canimentioning
confidence: 92%
“…Thus, in endemic areas, CME should be a top differential for persistent lymphocytosis in the dog [49]. Aplastic pancytopenia typifi es the myelosuppressive CME and the latter may be the major cause of canine pancytopenia in endemic areas [51]. Pancytopenia with normocellular BM may occur in acute CME, and is easily amenable to medical treatment [38].…”
Section: Hematologymentioning
confidence: 99%
“…We have read with keen interest the Letter to the Editor , commenting on our recent publication “Canine pancytopenia in a Mediterranean region: a retrospective study of 119 cases (2005‐2013) (Frezoulis et al . ) and thank you for giving us the opportunity to elaborate further on this issue.…”
mentioning
confidence: 99%